a.(1+i)/(2)

b. (1-i)/(2)

c. (5+i)/(2)

d. no solution

(3 - 2i) / (1 - i)

= [(3 - 2i)(1 + i)] / (1 - i)( 1 + i)

= (3 + 3i - 2i - 2i^{2}) / (1 - i^{2})

= (5 + i) / 2

a.(1+i)/(2)

b. (1-i)/(2)

c. (5+i)/(2)

d. no solution

Tutors, please sign in to answer this question.

(3 - 2i) / (1 - i)

= [(3 - 2i)(1 + i)] / (1 - i)( 1 + i)

= (3 + 3i - 2i - 2i^{2}) / (1 - i^{2})

= (5 + i) / 2

*i = √(-1) * --->* i ^{2} = - 1
*

3 – 2

———— =

1 –

(3 – 2

——————— =

(1 –

3 – 2

———————— =

1

The answer is (c)

## Comments

so whats the answer? i got b